THE ROLE OF SOCIOPRAGMATICS IN POLITICAL DISCOURSE: UNPACKING MEANING AND INFLUENCE - Abdiyev Mavlonbek Xolmurot o’g’li (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: In the realm of political discourse, language functions not merely as a means of communication but as a powerful tool that shapes public perception and action. The field of sociopragmatics, which examines how context influences the use and understanding of language, offers valuable insights into how politicians and political actors craft their messages to resonate with diverse audiences. This article explores the role of sociopragmatics in political discourse, highlighting its significance in framing political messages, negotiating power relations, and fostering public engagement.